1996
DOI: 10.1002/(sici)1097-0142(19960701)78:1<91::aid-cncr14>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neoadjuvant chemotherapeutic response of locally advanced breast cancer by magnetic resonance imaging

Abstract: BACKGROUND. The implementation of new treatment protocols for locally advanced breast cancer is currently limited by inaccurate evaluation of response to neoadjuvant chemotherapy. A recently developed dedicated breast magnetic resonance imaging (MRI) method (RODEO MRI) was evaluated as a tool for determining tumor response and extent of residual disease after neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
105
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(120 citation statements)
references
References 28 publications
9
105
0
6
Order By: Relevance
“…Although this study did not focus on the prognostic relationship among these findings, it is in consonance with other studies that have shown that the variety of pathologic responses *chi-square test; p < 0.05 significant **ANOVA one tailed; p < 0.05 significant seen indicates that the entire pre-chemotherapy tumor area should be removed [10,15]. For some authors, the diversity of pathologic findings indicates the need for mastectomy [16,17]. Other authors argue that the low recurrence rates reported in selected cases of T3 and T4 show that these patients could rather undergo conserving surgery [3,18].…”
Section: Discussionsupporting
confidence: 81%
“…Although this study did not focus on the prognostic relationship among these findings, it is in consonance with other studies that have shown that the variety of pathologic responses *chi-square test; p < 0.05 significant **ANOVA one tailed; p < 0.05 significant seen indicates that the entire pre-chemotherapy tumor area should be removed [10,15]. For some authors, the diversity of pathologic findings indicates the need for mastectomy [16,17]. Other authors argue that the low recurrence rates reported in selected cases of T3 and T4 show that these patients could rather undergo conserving surgery [3,18].…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have suggested that MRI is a more accurate method of delineating residual tumour following neoadjuvant chemotherapy than clinical, ultrasound or mammographic assessment (Boetes et al, 1995;Abraham et al, 1996;Drew et al, 1999Drew et al, , 2001Fischer et al, 1999;Balu-Maestro et al, 2002;Rieber et al, 2002;Cheung et al, 2003;Rosen et al, 2003;Martincich et al, 2004;Warren et al, 2004). Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that breast magnetic resonance imaging (MRI) is more accurate in the diagnosis of primary breast cancer (Cocconi et al, 1984;Gilles et al, 1994;Abraham et al, 1996;Drew et al, 1999) and we therefore, wished to assess its use in the evaluation of tumour response and residual tumour size following chemotherapy when compared with conventional imaging. More accurate information may enable appropriate planning of surgery including BCS, minimising re-excision rates while maintaining the efficacy and possibility of cure.…”
mentioning
confidence: 99%
“…23 With a sensitivity ranging from 63% to 100%, the MRI scan seems to be an accurate method of delineating residual tumor volume after neoadjuvant therapy for large breast tumors. [25][26][27][28][29] In our study, clinicopathologic sizes were well correlated with breast imaging, which was performed to rule out breast-preserving surgery. However, postchemotherapy mammograms could show extensive calcifications or stable disease whereas histopathologic results revealed breast-conserving surgery feasibility.…”
Section: Discussionmentioning
confidence: 75%